1995
DOI: 10.1159/000188643
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Trehalase Activity Is a Useful Marker of Renal Proximal Tubular Damage in Newborn Infants

Abstract: To clarify the reliability of urinary trehalase activity as a marker of cellular proliferation and/or damage of renal proximal tubules, the activity was examined in healthy newborn infants or infants treated with tobramycin, a drug known as causing tubular cell damage. Eighty-one newborn infants (56 mature infants and 25 premature infants) were enrolled in the study. Urinary trehalase was examined using a spot urine sample during the first 7 days of age and on the 10th day of age. A good positive correlation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…In this connection, we [6] previously showed that treatment of mature infants with ampicillin and tobramycin, which are known to cause tubular cell damage, resulted in an increase in urinary trehalase, and the extent of this eleva tion was greater than that of urinary NAG. Nishimura et al [23] reported that a significant increase in urinary trehalasc in a cadmium-administered rabbit was accompa nied by a decrease of trehalase in renal brush border mem brane.…”
Section: Urinary Trehalase In Patients With Renal Tubular Damagementioning
confidence: 89%
See 3 more Smart Citations
“…In this connection, we [6] previously showed that treatment of mature infants with ampicillin and tobramycin, which are known to cause tubular cell damage, resulted in an increase in urinary trehalase, and the extent of this eleva tion was greater than that of urinary NAG. Nishimura et al [23] reported that a significant increase in urinary trehalasc in a cadmium-administered rabbit was accompa nied by a decrease of trehalase in renal brush border mem brane.…”
Section: Urinary Trehalase In Patients With Renal Tubular Damagementioning
confidence: 89%
“…Based on these observations, it is clear that the elevation of urinary trehalase reflects the extent of proximal tubular damage. We previously found that uri nary trehalase activity of premature infants is lower than that of mature infants or adults [6], Therefore, urinary tre halase is a specific indicator to estimate renal tubular development in infants.…”
Section: Urinary Trehalase In Patients With Renal Tubular Damagementioning
confidence: 96%
See 2 more Smart Citations
“…In cadmium poisoned patients urinary trehalase activity is found to be significantly low at the later stage of the disease due to reduced tubular cell mass. Study of urinary trehalase has been done as an indicator of tubular damage in newborn infants and infants treated with drug which causes tubular damage (10) Little information is available on the value of these tests for detecting involvement of tubular dysfunction in nephrotic syndrome patients.…”
Section: Introductionmentioning
confidence: 99%